Quality Management Model Based on Lean Six Sigma for Reducing Returns of Defective Clothing Articles in SMEs from the Clothing Industry - Pacheco-Bonilla, Maday (2020)
El texto completo de este trabajo no está disponible en el Repositorio Académico UPC por restricciones de la casa editorial donde ha sido publicado.